Analisis Pengaruh Fluktuasi Mata Uang Asing terhadap Perdagangan Internasional dan Dampaknya terhadap Penerimaan Devisa Negara - Maswir, Mulyadi (Eko dan Bisnis: Riau Economic and Business Review, 2024)
This study aims to analyze the impact of foreign exchange rate fluctuations on international trade and its effects on the country's foreign exchange earnings. Exchange rate fluctuations can influence the competitiveness of export and import prices, ultimately affecting the trade balance and foreign exchange earnings. The study utilizes data on exchange rates, trade volumes, and foreign exchange earnings from 2018 to 2023. The analysis results indicate that exchange rate volatility has a significant impact on the growth of international trade and the country's foreign exchange earnings